2013
DOI: 10.3354/ame01613
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and temporal dynamics of Southern California coastal marine cyanophage isolates

Abstract: Marine ecosystems contain an immense diversity of phages, many of which infect the cyanobacteria responsible for a portion of oceanic primary productivity. To add to the growing body of research on the dynamics and diversity of these cyanophages, we measured cyanophage abundance, diversity, and community composition monthly for 15 mo at 3 coastal locations in Southern California, USA. We characterized over 900 individual cyanophages, isolated on Synechococcus sp. WH7803, by amplifying and sequencing 2 differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 69 publications
(107 reference statements)
2
25
0
Order By: Relevance
“…In fact, we found that 90% of these psbA sequences (56 out of 62) had a GC content below 46% and were thus out of the percentage range (46 to 51%) found in marine Synechococcus phages (36). Our results echo the other freshwater studies (11,41), where low GC content has also been detected in some Synechococcus-virus-like psbA sequences and in the only known characterized freshwater Synechococcus phage, S-CRM01 (44.6%), at the same 729-nt region. Together, these results suggest that freshwater Synechococcus phages might have a lower GC content in psbA sequences than their marine counterparts, and this may be a result of a lower GC content in their Synechococcus hosts.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…In fact, we found that 90% of these psbA sequences (56 out of 62) had a GC content below 46% and were thus out of the percentage range (46 to 51%) found in marine Synechococcus phages (36). Our results echo the other freshwater studies (11,41), where low GC content has also been detected in some Synechococcus-virus-like psbA sequences and in the only known characterized freshwater Synechococcus phage, S-CRM01 (44.6%), at the same 729-nt region. Together, these results suggest that freshwater Synechococcus phages might have a lower GC content in psbA sequences than their marine counterparts, and this may be a result of a lower GC content in their Synechococcus hosts.…”
Section: Discussionsupporting
confidence: 71%
“…This is a common issue of diversity studies through the culture-independent approach by using PCR, since the validity of the primers depends on a limited number of isolates. Recently, Clasen et al (11) employed the isolation-based/ culture-dependent approach to examine marine cyanomyoviruses infecting Synechococcus sp. WH7803 and revealed important cooccurring cyanomyovirus genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, psbA was also investigated, but it proved less well suited for species diversity studies, since it was found in phages belonging to only one of the two clades. Using two signature genes, g20 and psbA, a collection of over 900 Synechococcus phages, collected at three different coastal sites over a 15-month period, was investigated (92). No spatial variations were found, but distinct seasonal communities were observed, with higher abundances in summer, consistent with previous studies described above (15)(16)(17)(18)77).…”
Section: Multi-signature Gene Studiessupporting
confidence: 64%